2022
DOI: 10.3390/su14074175
|View full text |Cite
|
Sign up to set email alerts
|

Design Analysis of an Optimal Microgrid System for the Integration of Renewable Energy Sources at a University Campus

Abstract: The integration of renewable energy sources (RESs) is a strategic goal in Saudi Arabia. The energy source diversification plan comprises the penetration of various technologies, including solar photovoltaic (PV) and wind energy. In this research, an optimal microgrid system design is proposed and analyzed at the Islamic University of Madinah. The research intends to facilitate the decision-making process in the incorporation of RESs in Saudi universities. A pilot project has been established at the Faculty of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The results showcased a sustainable energy solution with a peak electrical load of 9.958 MW, a net present cost (NPC) of USD 30M, and a levalized cost of energy (LCOE) at 0.00274 USD/kWh. The authors of [10] found that integrating renewable energy sources (RESs), specifically solar PV and wind energy, helped with achieving strategic objectives in Saudi Arabia. An optimal MG system for the Islamic University of Madinah was studied with the following three alternatives analyzed: PV, WT, and hybrid systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showcased a sustainable energy solution with a peak electrical load of 9.958 MW, a net present cost (NPC) of USD 30M, and a levalized cost of energy (LCOE) at 0.00274 USD/kWh. The authors of [10] found that integrating renewable energy sources (RESs), specifically solar PV and wind energy, helped with achieving strategic objectives in Saudi Arabia. An optimal MG system for the Islamic University of Madinah was studied with the following three alternatives analyzed: PV, WT, and hybrid systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The LCOE for the other institutions was as follows: Tabuk's is $0.0714; Sattam's is $0.0753; and Jeddah's is $0.0702. At the Islamic University of Madinah in KSA, AlKassem et al (2022) examined the design of a microgrid system. For the PV system, wind system, and hybrid system, three possibilities were examined, and their technical and economic performance was evaluated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many tools that can be used to obtain the optimal solution [30][31][32][33][34][35][36][37][38]. Among them is a powerful software tool to optimize hybrid renewables systems introduced by the National Renewable Energy Laboratory in the United States and is called the Hybrid Optimization Model for Electric Renewables.…”
Section: Optimization Approachmentioning
confidence: 99%